Comparative study on the clinical effect of preparing neobladder with different lengths of ileum - Zheng, Bin; Liu, Zhenghong; Wang, Heng; Wang, Jinxue; Zhang, Pu; Zhang, Dahong (Frontiers in Oncology, 2022)
Objective： To investigate the correlation between the volume of the radical cystectomy and the U-shaped ileal neobladder in situ and the function of the bladder. Methods: The clinical data of patients undergoing in situ U-shaped neobladder in our hospital were retrospectively analyzed. They were divided into two groups according to the length of the retained ileum. Group 1: The length of the ileum was 25-35cm (including 35cm), and the second group: the length of the ileum was 35-45cm. The basic information, cushion usage, urodynamic examination and complications of the two groups were obtained. Results: A total of 88 patients were included in the study, including 33 in the first group and 55 in the second group. There was no statistical difference in general data, lymph node collection, lymph node positive rate, positive margin rate, postoperative pathological stage, pathological grade, pathological type, intraoperative blood loss, blood transfusion, postoperative hospital stay, and complications between the two groups of patients. significance. Although the usage of urine pads in group 1 was more than that in group 2 in the short term after operation (P<0.05), it started from the third year after operation. Patients in group 1 used less cushion than group 2 (P<0.05). Urodynamic examination was performed on the patients, and the bladder function of group 1 maintained satisfactory time longer than that of group 2. The total number of deaths in the two groups was 12 and 23, respectively. The 5-year overall survival (OS) rate of group 1 was 53.60%, and the 5-year overall survival rate of group 2 was 52.80%. Conclusions: A new bladder formed by cutting the ileum with a length of 25-35 cm (including 35cm) has a longer time to maintain good bladder function than cutting the ileum with a length of 35-45 cm to produce a new bladder.